2021
DOI: 10.1080/20008198.2021.1943870
|View full text |Cite
|
Sign up to set email alerts
|

Is only one cognitive technique also effective? Results from a randomized controlled trial of two different versions of an internet-based cognitive behavioural intervention for post-traumatic stress disorder in Arabic-speaking countries

Abstract: Knaevelsrud (2021) Is only one cognitive technique also effective? Results from a randomized controlled trial of two different versions of an internet-based cognitive behavioural intervention for post-traumatic stress disorder in Arabic-speaking countries,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 50 publications
(79 reference statements)
3
9
1
Order By: Relevance
“…Participants were treatment-seeking individuals who completed an online screening survey to take part in an internet-based treatment for either post-traumatic stress disorder (PTSD) or depression in the Arabic language (approved by the Ethics Committee of the University of Leipzig, Germany: 236-11-22082011). The study has a cross-sectional design and is part of an open-label dissemination study of the included treatments [e.g., ( 22 24 )]. The dissemination study is being implemented in the context of a program that has been ongoing since 2008 and is conducted by a German psychosocial center that offers psychosocial treatment for victims of torture and war.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were treatment-seeking individuals who completed an online screening survey to take part in an internet-based treatment for either post-traumatic stress disorder (PTSD) or depression in the Arabic language (approved by the Ethics Committee of the University of Leipzig, Germany: 236-11-22082011). The study has a cross-sectional design and is part of an open-label dissemination study of the included treatments [e.g., ( 22 24 )]. The dissemination study is being implemented in the context of a program that has been ongoing since 2008 and is conducted by a German psychosocial center that offers psychosocial treatment for victims of torture and war.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they had to have experienced one or more losses of family members or friends. As only screening data were analyzed, the inclusion and exclusion criteria for the dissemination study of the treatments were not yet applicable [for exclusion criteria of the intervention see ( 22 )].…”
Section: Methodsmentioning
confidence: 99%
“…A small pilot study of a comparable programme for N = 15 Dari or Farsi speaking youths showed high drop-out rates (23). In two larger scale studies, Knaevelsrud and colleagues (24,25) could show that a guided online program led to large changes in PTSD symptoms in patients in war and conflict zones. Although very encouraging, the focus of these trials was on PTSD, excluding other very prevalent problems such as anxiety, depression, and substance abuse.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%
“…Over the past two decades, cognitive–behavioural methods, including exposure-based and cognitive techniques for the treatment of PTSD, have been adapted for delivery in web-based settings (e.g. Böttche et al, 2021 ; Spence et al, 2014 ; Stein et al, 2023 ). Providing treatment to individuals experiencing mental health problems through the internet presents significant advantages, particularly for those with limited access to face-to-face treatment.…”
Section: Introductionmentioning
confidence: 99%